The new GeoModel suite, a lightweight detector description and visualization toolkit for HEP. Issue 1 (1st February 2023) - Bandieramonte, M; Bianchi, R M; Boudreau, J; Dell'Acqua, A; Tsulaia, V
Abstract: The GeoModel toolkit is an open-source suite of standalone tools that provides the user with lightweight tools to describe, visualize, test, and debug detector descriptions and geometries for HEP standalone studies and experiments. GeoModel has been designed with independence and responsiveness in mind and offers a development environment free of other large HEP tools and frameworks, and with a very quick development cycle. With very few and lightweight dependencies, GeoModel is easy to install on all systems, in a modular way; and pre-compiled binaries are provided for the major platforms, for a quick and easy installation. Coded entirely in C++, GeoModel offers the user tools to describe geometries inside C++ code or in external XML files, create persistent representation with a low disk footprint and interactively visualize and inspect the geometry in a 3D view. It also offers a plugin mechanism and an optional Geant4 application to simulate the described geometry in a standalone environment. GeoModel has been developed as part of the software for the ATLAS experiment at the LHC, and evolved towards an experiment-independent toolkit. In this contribution, we describe all the available tools, with a focus on the latest additions, which provide users with more visualization, debug, and simulation tools.